A 24-chromosome FISH technique in preimplantation genetic diagnosis: validation of the method. (June 2015) - Fernández, Silvia F.; Toro, Estefanía; Colomar, Ana; López-Teijón, Marisa; Velilla, Esther
Abstract Embryo screening for aneuploidy (AS) is part of preimplantation genetic diagnostics (PGD) and is aimed at improving the efficiency of assisted reproduction. Currently, several technologies, including the well-established fluorescence in situ hybridization (FISH) technique, cover the screening of all chromosomes in a single cell. This study evaluates a novel 24-chromosome FISH technique protocol (FISH-24). A total of 337 embryos were analyzed using the traditional 9-chromosome FISH technique (FISH-9) while 251 embryos were evaluated using the new FISH-24 technique. Embryos deemed nontransferable on Day 3 were cultured in vitro to Day 5 of development, then fixed and reanalyzed according to the technique allocated to each treatment cycle (107 embryos analyzed by FISH-9 and 111 by FISH-24). The global error rate (discrepancy between Day 3 and Day 5 results for a single embryo) was 2.8% after FISH-9 and 3.6% after FISH-24, with a p value of 0.95. Thus, we have established and validated a 24-chromosome FISH-based single cell aneuploidy screening technique, showing that the error rate obtained for FISH-24 is independent of the number of chromosomes analyzed and equivalent to the error rate observed for FISH-9, as a useful tool for chromosome segregation studies and clinical use.